Choosing Surgery: Identifying Factors Leading to Increased General Surgery Matriculation Rate. Issue 3 (March 2017) - Pointer, David T.; Freeman, Matthew D.; Korndorffer, James R.; Meade, Peter C.; Jaffe, Bernard M.; Slakey, Douglas P.
Tulane graduates have, over the past six years, chosen general surgical residency at a rate above the national average (mean 9.6% vs 6.6%). With much of the recent career choice research focusing on disincentives and declining general surgery applicants, we sought to identify factors that positively influenced our students' decision to pursue general surgery. A 50-question survey was developed and distributed to graduates who matched into a general surgery between the years 2006 and 2014. The survey evaluated demographics, exposure to surgery, and factors affecting interest in a surgical career. We achieved a 54 per cent (61/112) response rate. Only 43 per cent considered a surgical career before medical school matriculation. Fifty-nine per cent had strongly considered a career other than surgery. Sixty-two per cent chose to pursue surgery during or immediately after their surgery clerkship. The most important factors cited for choosing general surgery were perceived career enjoyment of residents and faculty, resident/faculty relationship, and mentorship. Surgery residents and faculty were viewed as role models by 72 and 77 per cent of responders, respectively. This study demonstrated almost half of those choosing a surgical career did so as a direct result of the core rotation experience. We believe that structuring the medical student education experience to optimize the interaction of students, residents, and faculty produces a positive environment encouraging students to choose a general surgery career.